In memoriam - Mladenović, Branka (Yugoslav Journal of Operations Research; Vol 27 No 4 (2017), 2017)
This year we have lost two prominent members of our Editorial Board, professor Bernard Roy and professor Klaus Ritter, who significantly contributed to the international reputation of YUJOR, whereon we are deeply grateful. BERNARD ROY 1934 - 2017 Bernard Roy was born at Moulins in France. He graduated in Mathematics in 1954 from Université de Paris, obtained a postgraduate degree in Applied Mathematics in 1957 from the "Institut de Statistiques de l'Université de Paris", followed by a Ph.D. in Graph Theory in 1961. In 1957 he started working, first for the CNRS and then for SEMA METRA International, among the first companies to introduce, at European level, the use of Operations Research and Management Science in real world problems. Bernard Roy was editor in chief of the quarterly journal "Revue Scientifique de SEMA METRA" published between 1964 and 1977, one of the most innovative journals in OR in Europe. In 1972 Roy left SEMA joining the newly established "Université Paris Dauphine", where he became a full professor in 1974. In the same year, he established a research center, which is known as LAMSADE, as well as one of the first Masters Degrees in France in Operations Research and Management Science, both of them being active today and internationally recognized. Professor Roy retired in 2001 turning to emeritus, but until his very last days, he was very active in research and consulting. Bernard Roy's contributions in Operations Research started from scheduling theory where he contributed one of the most original methods based on an "activity on node" formulation. Later on, he contributed to graph theory with several outstanding results summarised in a two-volume book. Bernard Roy is internationally recognized as being the founder of a distinguished school in Multiple Criteria Decision Analysis as well as for creating a series of Multiple Criteria Decision Aiding Methods, based on concepts and tools from social choice theory and graph theory. Bernard Roy was President of AFCET (the French society representing OR at that time) in 1976-78 as well as Honorary President of ROADEF (the French OR society). Also, he was the president of EURO in the years 1985-86. He received the EURO Gold Medal in 1992, and the International MCDM Society Gold Medal in 1995, as well as the EURO Distinguished Service Medal in 2015. He was received as Docteur Honoris Causa in six Universities (VUB, Liège, Fribourg, Poznań, Laval and Crete). Professor Roy leaves behind him an immense scientific legacy to be continued by the tens of scholars trained by him and the hundreds of researchers and practitioners who have been influenced by his original vision of Operations Research. KLAUS RITTER 1936 - 2017 Klaus Ritter, born in Sackingen in 1936, studied mathematics and physics at the Munich Ludwig Maximilian University and the University of Freiburg. He obtained his doctorate in 1964 from the University of Freiburg, supervised by H. Gortler. After research in the area of Mathematical Programming at the University of Wisconsin in Madison, USA (1965-1967), and the Technical University of Karlsruhe (1967-1969), where he habilitated in 1968, Ritter returned to the United States - as an associate professor at the University of Wisconsin (1969-1970). Next three years he has spent at Rutgers University, New Brunswick, first as an associate professor (1970-1972) and as a professor (1972-1973). In 1973 he accepted a call from the University of Stuttgart, where he served as a professor from 1973-1981. In 1981 he moved to the Technical University of Munich, where he held the Chair of Applied Mathematics and Mathematical Statistics until his retirement. From 1982-1986 he was a visiting professor at University of Waterloo, Canada. Klaus Ritter retired in 2004, turning to emeritus, but he remained active in research and in mathematics education of vocational school teachers and teacher training. Klaus Ritter has done important work in a variety of areas, especially linear and nonlinear optimization and also in connection with statistics and parallel computing. His contributions to convergence analysis of nonlinear programming methods were instrumental in giving the field of Nonlinear Optimization its present look. At a very early stage, in the 1980s, he recognized the progressive importance of parallel computers and focused on the development of parallel numerical methods. In addition to his research and university teaching duties, he has put a lot of effort in applying mathematical methods to problems of industry. He has strongly influenced the development of Operations Research in Germany by bringing new research ideas from his study visits to the USA and Canada. In spring 1974 he held a three-week course "Mathematical Programming" at the Faculty of Mathematics at University of Belgrade, which has resulted in the introduction of the new area into curricula of undergraduate and master studies. Together with Werner Oettli, in 1975 he organized the workshop "Numerical Methods of Optimization and Operations Research" at the world-famous Mathematical Research Institute of Oberwolfach, whose success has contributed to establishing regular Oberwolfach workshops on "Mathematical Optimization". In 1979 and 1981 the workshops were organized by Konig, Korte, Riter, in 1983, 1985, 1988, 1990, 1992, 1995 by Korte and Ritter, and in 1997 by Korte, Ritter and Dennis. These workshops gathered most prominent researchers from all over the world working in discrete and continuous optimization, giving them an excellent opportunity for the exchange of ideas, and had a strong impact to the development of the field of Mathematical Programming. Klaus Ritter will be remembered with gratitude by more than 100 master and numerous Ph.D. students who worked under his supervision and were influenced by his original mathematical ideas and by generations of researchers who had a privilege to attend Oberwolfach workshops organized by him.